Antioxidant capacity and phytochemical characterization of Spathodea campanulata growing in different climatic zones in Brazil - Santos, Valter H.M. (2020)
The aim of present study was evaluating the antioxidant activity and real content of phytochemicals of Spathodea campanulata from different climatic regions (two subtropical and one tropical area/cities) at Brazil. Samples of leaves, flowers and nectars from S. campanulata were tested for total phenolic content and in vitro antioxidant activity by ORAC (Oxygen Radical Absorbance Capacity), FRAP (Ferric Reducing Antioxidant Power) and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. The phytochemical tests were carried out by two different chromatographic methods of detection (PDA and ECD) in HPLC for quantify the phenolic compounds content and one methods (PDA) in HPLC for quantify the carotenoids content. The results of the study indicate that mainly the samples of leaves and flowers of S. campanulata have significant total phenolic content and the antioxidant activity independent of analyzed city. In relation to phytochemical tests, the leaves samples from Assis city presented the higher total content of phenolic compounds among analyzed cities independent of detector (PDA and ECD). Total content of carotenoids was higher the leaves samples from Londrina city. This study reveals that the flowers and leaves of S. campanulata present substances with antioxidant potential, as noted in the antioxidant tests and phytochemical screening. Thus, Spathodea campanulata can be considered a good source of antioxidants independent of the occurrence of the individual in different climatic regions of Brazil.